PTU-086 Does an effective hospital alcohol liason service have an impact on hcc surveillance. (17th June 2017) - Patel, V; Butt, A-T; Dillon, C; Pritchard, C; Sennitt, H; Carey, H; Lo, A; Aung, P; Hancock, A
Abstract : Introduction: Hepatocellular Carcinoma (HCC) is the 17th most common cancer in the UK (new diagnoses, 2014) 1 . Between 2002–2004 and 2011–2013 average incidence of primary liver cancer increased significantly: 55% among males; 46% among females 2 . Early detection and intervention improves patient outcomes. In April 2013 Tameside General Hospital introduced a Hospital Alcohol Liaison Service (HALS) which screens all patients admitted with alcohol related harms. HALS educates patients, advises on their inpatient management, runs the ambulatory clinic, and facilitates discharge to community services promptly and appropriately. Their goal was to reduce liver harm and related mortality. We believe this increases compliance with HCC surveillance programmes. Method: We have conducted a retrospective audit of all cases coded as "Cirrhosis" (ICD-10: K70.3, K74.6) between 2012 to 2016 at a DGH in Greater Manchester. Each EPR was accessed to ascertain timing of alpha-fetoprotein (AFP) testing, timing of imaging of the liver, and documented diagnosis. Current BSG guidelines suggest 6 monthly AFP and ultrasound scan (USS) to surveil formation of HCC in high risk population groups. For the purposes of our audit, we have attempted to identify whether patients were receiving AFP and liver imaging in a 12 monthly period. Search criteria were broadened to include MRI and CT images of the liver as these would be non-inferior to USS in terms of assessing cirrhosis and presence of focal lesions. Results: An increasing number of patients were given diagnoses of cirrhosis per year: These numbers of patients required surveillance: These numbers of patients received surveillance: Conclusion: We conclude introduction of a HALS service improves compliance with surveillance in cirrhotic patients. This will increase early detection of HCC, increase treatment options, and decrease mortality. References: . Cancer Research UK, http://www.cancerresearchuk.org/sites/default/files/cstream-node/inc_20common_persons_I14_0.pdf, [Accessed Feb. 2017] . Cancer Research UK, http://www.cancerresearchuk.org/health-professional/cancer-statistics/incidence/common-cancers-compared#heading-Three [Accessed Feb. 2017] Disclosure of Interest: None Declared